Augmented reality warnings in vehicles: Effects of modality and specificity on effectiveness. (April 2017) - Schwarz, Felix; Fastenmeier, Wolfgang
Highlights: Effects of modality (visual vs. auditory) and specificity (low vs. high) are compared for Car-to-X based warnings. Sight obstruction and false alarms are identified as crucial context parameters. Augmented reality warning concepts are proposed and analyzed as specific warnings. Visual specific warnings consistently improve various measures of effectiveness. Points to important impact of specific depiction of information besides modality and specificity. Abstract: In the future, vehicles will be able to warn drivers of hidden dangers before they are visible. Specific warning information about these hazards could improve drivers' reactions and the warning effectiveness, but could also impair them, for example, by additional cognitive-processing costs. In a driving simulator study with 88 participants, we investigated the effects of modality (auditory vs. visual) and specificity (low vs. high) on warning effectiveness. For the specific warnings, we used augmented reality as an advanced technology to display the additional auditory or visual warning information. Part one of the study concentrates on the effectiveness of necessary warnings and part two on the drivers' compliance despite false alarms. For the first warning scenario, we found several positive main effects of specificity. However, subsequent effects of specificity were moderated by the modality of the warnings. The specific visual warnings were observed to have advantages over the three other warning designs concerning gaze and braking reaction times, passing speeds and collision rates. Besides the true alarms, braking reaction times as well as subjective evaluation after these warnings were still improved despite false alarms. The specific auditory warnings were revealed to have only a few advantages, but also several disadvantages. The results further indicate that the exact coding of additional information, beyond its mere amount and modality, plays an important role. Moreover, the observed advantages of the specific visual warnings highlight the potential benefit of augmented reality coding to improve future collision warnings.